2022
DOI: 10.1136/bmjopen-2022-066288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on timeliness and equity of measles, mumps and rubella vaccinations in North East London: a longitudinal study using electronic health records

Abstract: ObjectivesTo quantify the effect of the COVID-19 pandemic on the timeliness of, and geographical and sociodemographic inequalities in, receipt of first measles, mumps and rubella (MMR) vaccination.DesignLongitudinal study using primary care electronic health records.Setting285 general practices in North East London.ParticipantsChildren born between 23 August 2017 and 22 September 2018 (pre-pandemic cohort) or between 23 March 2019 and 1 May 2020 (pandemic cohort).Main outcome measureReceipt of timely MMR vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…Large studies have shown that the coronavirus pandemic negatively impacted routine vaccination rates in countries around the world [25][26][27][28]. Consistent with previous research, the decrease in coverage in LAC countries and territories likely stems from service disruptions, a lack of vaccine availability, the population's fear of visiting health centers, and the diversion of resources to pandemic-related activities [25][26][27][28][29][30]. This being acknowledged, the fact that eight LAC countries and territories had no decreases in DPTcv3 coverage suggests that some countries may have been able to quickly recover from service disruptions in early 2020 due to their strong immunization programs [25], relatively mild income inequality, or other factors.…”
Section: Discussionsupporting
confidence: 59%
“…Large studies have shown that the coronavirus pandemic negatively impacted routine vaccination rates in countries around the world [25][26][27][28]. Consistent with previous research, the decrease in coverage in LAC countries and territories likely stems from service disruptions, a lack of vaccine availability, the population's fear of visiting health centers, and the diversion of resources to pandemic-related activities [25][26][27][28][29][30]. This being acknowledged, the fact that eight LAC countries and territories had no decreases in DPTcv3 coverage suggests that some countries may have been able to quickly recover from service disruptions in early 2020 due to their strong immunization programs [25], relatively mild income inequality, or other factors.…”
Section: Discussionsupporting
confidence: 59%
“…Just 79% of children in northeast London received their first measles, mumps and rubella (MMR) vaccine on time prior to the COVID-19 pandemic, with timeliness decreasing most in City & Hackney during the pandemic ( Firman, 2022 ). In October–December 2022, Hackney GP surgeries recorded practice-level hexavalent vaccine coverage rates by 12 months of age as low as 16.7% and 23.4% ( United Kingdom Health Security Agency, 2023a ).…”
Section: Discussionmentioning
confidence: 99%
“…8 We have recently assessed the impact of the COVID-19 pandemic in north east London (NEL), and found a 4% decrease in MMR timeliness in 2020 compared with the previous year, and marked inequalities between children living in the least and most deprived areas. 9 …”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with findings from a study of general practices in England, however, this did not include many practices in London, which has historically the lowest childhood vaccination rates in the UK 8. We have recently assessed the impact of the COVID-19 pandemic in north east London (NEL), and found a 4% decrease in MMR timeliness in 2020 compared with the previous year, and marked inequalities between children living in the least and most deprived areas 9…”
Section: Introductionmentioning
confidence: 99%